2019
DOI: 10.1109/access.2019.2904943
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Virtual Inertia Control Strategy of VSG for Micro-Grid Based on Improved Bang-Bang Control Strategy

Abstract: With the increasing capacity of new energy in the power system, new energy cannot provide support for the system frequency directly. This characteristic of new energy affects the frequency stability of the power system. Therefore the control strategy of a virtual synchronous generator (VSG) is proposed to improve the frequency stability of the system. An adaptive virtual inertia control strategy based on an improved bang-bang control strategy for a micro-grid is presented. On one hand, it can make full use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 18 publications
0
72
0
Order By: Relevance
“…The results showed that the VSG control had greater inertia than the droop control and higher frequency stability. However, the power allocation accuracy of VSG control was greatly affected by the line parameters, and the active power in VSG control was more oscillating than the droop control strategy [24]. In order to solve the problem of unbalanced parallel output power of multiple energy storage batteries, references [25], [26] proposed a dynamic droop control strategy applying in the energy storage system (ESS), which dynamically allocated energy storage according to the state of charge (SOC) of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the VSG control had greater inertia than the droop control and higher frequency stability. However, the power allocation accuracy of VSG control was greatly affected by the line parameters, and the active power in VSG control was more oscillating than the droop control strategy [24]. In order to solve the problem of unbalanced parallel output power of multiple energy storage batteries, references [25], [26] proposed a dynamic droop control strategy applying in the energy storage system (ESS), which dynamically allocated energy storage according to the state of charge (SOC) of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [20], active power and reactive power independent controls are discussed by analysing the power coupling mechanism of VSG in medium-and low-voltage microgrids, but analysis for high-voltage microgrid and transient stability are not discussed in it. Additionally, adaptive inertia strategies for VSG with different control schemes are presented in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the frequency fluctuation of the grid cannot be damped by inertia effectively [4]. As a result, the power system under high penetration of RES is expected to become less predictable and unreliable dynamic non-linear system [5]. Recent researches have been focused on the adoption of a control scheme for inverters to compensate for the loss of inertia by mimicking the SM.…”
Section: Introductionmentioning
confidence: 99%